Sharp inequality of three point Gauss-Legendre quadrature rule - Kashuri,Artion (Universidad Católica del Norte, Departamento de Matemáticas, 2020)
Abstract: An interesting identity for 3-point Gauss-Legendre quadrature rule using functions that are n-times differentiable. By applying the established identity, a sharp inequality which gives an error bound for 3-point Gauss-Legendre quadrature rule and some generalizations are derived. At the end, an application in numerical integration is given.